Экспертное оценивание многофакторных рисков в технологическом предвидении - Панкратова, Н.Д.; Недашковская, Н.И. (Видавничий дім "Академперіодика" НАН України, 2007)
The multiple-factor risk evaluation in the technology foresight of prospects of the evolution of complex innovation systems is proposed. The risk of unpredictable situations and the force majeure risk are analyzed with the help of the modified BOCR AHP methodology. A system of indices for information risk evaluation on different information levels, such as point, interval and fuzzy expert estimates taking into account the probability distribution of expert information is developed.